Multiplicity dependence of charged-particle jet production in pp collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (The European physical journal. C, Particles and fields, 2022)
The multiplicity dependence of jet production in pp collisions at the centre-of-mass energy of s√=13 TeV is studied for the first time. Jets are reconstructed from charged particles using the anti-kT algorithm with resolution parameters R varying from 0.2 to 0.7. The jets are measured in the pseudorapidity range |ηjet|<0.9−R and in the transverse momentum range 5<pchT,jet<140 GeV/c. The multiplicity intervals are categorised by the ALICE forward detector V0. The pT differential cross section of charged-particle jets are compared to leading order (LO) and next-to-leading order (NLO) perturbative quantum chromodynamics (pQCD) calculations. It is found that the data are better described by the NLO calculation, although the NLO prediction overestimates the jet cross section below 20 GeV/c. The cross section ratios for different R are also measured and compared to model calculations. These measurements provide insights into the angular dependence of jet fragmentation. The jet yield increases with increasing self-normalised charged-particle multiplicity. This increase shows only a weak dependence on jet transverse momentum and resolution parameter at the highest multiplicity. While such behaviour is qualitatively described by the present version of PYTHIA, quantitative description may require implementing new mechanisms for multi-particle production in hadronic collisions.